Synthesis of reusable silicone foam containing carbon nanotubes for oil spill remediation. Issue 14 (28th November 2017) - Piperopoulos, Elpida; Calabrese, Luigi; Mastronardo, Emanuela; Proverbio, Edoardo; Milone, Candida
ABSTRACT: The aim of this work is the synthesis of silicone foam containing carbon nanotubes (CNT) for oil spills remediation. The CNT silicone foams are obtained by foaming a solution of a silicone matrix with CNT filler (5.6 wt %) in presence of a Sn‐based catalyst. Pristine and functionalized CNT have been used. All the obtained materials present a foam morphology with an open cell structure. Each foam is tested in four commonly used oils (kerosene, pump oil, naphtha, and crude oil). Among all, the foam filled with pristine CNT shows the highest sorption capacity (800 wt % in virgin naphtha) and an excellent reusability (up to 10 times). © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46067. Abstract :